2022
DOI: 10.3390/ijms231911091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dried Onion Powder and Quercetin on Obesity-Associated Hepatic Menifestation and Retinopathy

Abstract: Onion (Allium cepa L.), rich in flavonoids (particularly quercetin), reportedly has anti-obesity properties, but the underlying mechanisms and associated health issues remain unclear. In this study, we compared the effects of dried onion powder (DO) with that of quercetin on high-fat diet (HFD)-induced obesity, nonalcoholic fatty liver disease, and retinal neovascularization. Briefly, rats (n = 9–10 per group) were divided into control, HFD alone (43% fat), HFD + DO (1% DO), HFD + 5DO (5% DO, w/w), and HFD + q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In this review, 22% of the selected articles showed an improvement in the lipid profile, especially in LDL levels, of animals supplemented with onion oil compared to the group that was submitted only to a high-fat diet, confirming the protective effect of onion (Yang et al, 2018). Also, studies have demonstrated improvements in all lipid profiles, with a decreased serum determination of total cholesterol and TG, and an increase in HDL-C, confirming that animals benefited from the powder, tea, oil or extracts of onion concentrated of protocatechuic acid (Benítez et al, 2012;Matsunaga et al, 2014;Emamat et al, 2018;Yang et al, 2018;Grzelak-Błaszczyk et al, 2020;Yu et al, 2021;Chang et al, 2022;Momoh et al,2022).…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…In this review, 22% of the selected articles showed an improvement in the lipid profile, especially in LDL levels, of animals supplemented with onion oil compared to the group that was submitted only to a high-fat diet, confirming the protective effect of onion (Yang et al, 2018). Also, studies have demonstrated improvements in all lipid profiles, with a decreased serum determination of total cholesterol and TG, and an increase in HDL-C, confirming that animals benefited from the powder, tea, oil or extracts of onion concentrated of protocatechuic acid (Benítez et al, 2012;Matsunaga et al, 2014;Emamat et al, 2018;Yang et al, 2018;Grzelak-Błaszczyk et al, 2020;Yu et al, 2021;Chang et al, 2022;Momoh et al,2022).…”
Section: Discussionmentioning
confidence: 68%
“…The main benefits of onion and its by-products, found in this review, lipid profile and cardiovascular risk with decreased total cholesterol, low-density lipoprotein cholesterol (LDL-C), triglycerides (TG), atherosclerosis index and aorta elastic modulus, and increased high-density lipoprotein cholesterol (HDL-C) (Hamauzu et al, 2011;Benítez et al, 2012;Matsunaga et al, 2014;Emamat et al, 2018;Yang et al, 2018;Grzelak-Błaszczyk et al, 2020;Yu et al, 2021;Momoh et al, 2022;Chang et al, 2022).…”
Section: Eligibility Criteriamentioning
confidence: 87%
See 3 more Smart Citations